Use of experiential methods for learning competencies related to specialized social intervention in drug addiction: a qualitative study. - Calvo, Fran (Social Work Education, 2026)
This qualitative research explores the educational impact of experiential activities in an elective module on social intervention in drug addiction among University of Girona students pursuing degrees in Social Education and Social Work. Through four focus groups involving 73 participants, comprising 38 Social Education and 35 Social Work students, thematic analysis was employed to assess their experiences. Key findings indicate that role-playing activities were instrumental in enhancing professional competencies and confidence among students in addressing real-world drug addiction cases. Participants highlighted the mandatory nature of these activities as beneficial for overcoming initial apprehensions, despite facing challenges such as embarrassment and fear of exposure. The experiential exercise involving total abstinence from drugs for a semester provided a profound insight into addiction complexities. Effective group support was identified as crucial in managing emotional and logistical obstacles throughout the semester. Incorporating experiential methods like role-playing and drug abstinence can significantly augment practical skills and empathy among students. This research underscores the importance of structured implementation and adequate support to optimize such educational approaches, thereby better preparing students for professional challenges in social disciplines.